Immune checkpoint B7‐H3 protein expression is associated with poor outcome and androgen receptor status in prostate cancer. Issue 12 (14th June 2021) - Nunes‐Xavier, Caroline E.; Kildal, Wanja; Kleppe, Andreas; Danielsen, Håvard E.; Wæhre, Håkon; Llarena, Roberto; Mælandsmo, Gunhild M.; Fodstad, Øystein; Pulido, Rafael; López, José I.
Abstract: Background: Novel immune checkpoint‐based immunotherapies may benefit specific groups of prostate cancer patients who are resistant to other treatments. Methods: We analyzed by immunohistochemistry the expression of B7‐H3, PD‐L1/B7‐H1, and androgen receptor (AR) in tissue samples from 120 prostate adenocarcinoma patients treated with radical prostatectomy in Spain, and from 206 prostate adenocarcinoma patients treated with radical prostatectomy in Norway. Results: B7‐H3 expression correlated positively with AR expression and was associated with biochemical recurrence in the Spanish cohort, but PD‐L1 expression correlated with neither of them. Findings for B7‐H3 were validated in the Norwegian cohort, where B7‐H3 expression correlated positively with Gleason grade, surgical margins, seminal vesicle invasion, and CAPRA‐S risk group, and was associated with clinical recurrence. High B7‐H3 expression in the Norwegian cohort was also consistent with positive AR expression. Conclusion: These results suggest distinct clinical relevance of the two immune checkpoint proteins PD‐L1 and B7‐H3 in prostate cancer. Our findings highlight B7‐H3 as an actionable novel immune checkpoint protein in prostate cancer.